A Meta-analysis of acupoint application in the treatment of dysphagia after stroke (穴位贴敷治疗脑卒中后吞咽障碍的Meta分析) - SI Huijie (佀惠婕); LIAO Ruoyi (廖若夷); YU Yanlan (余艳兰); GAO Ziqi (高子琪); LIU Bin (刘彬); GUO Yuan (郭元) (中西医结合护理)
Objective To systematically evaluate the efficacy of acupoint application in the treatment of post-stroke dysphagia. Methods PubMed, Embase, the Cochrane Library, Web of Science, CNKI, VIP, Wanfang databases and CMB were searched for studies on acupoint application in the treatment of post-stroke dysphagia. The search time limit was from the establishment of the database to January 31, 2023. Two researchers independently screened the literature, extracted data and evaluated the methodological quality. RevMan 5. 4 software was used for meta-analysis. Results A total of 11 RCTS/CCTS involving 1018 patients were included. Acupoint application in the treatment of dysphagia after stroke was superior to the control group in the total effective rat［OR=4. 16, 95% CI(2. 65, 6. 53), Z=6. 21(P＜0. 01)］, cure rate［OR=1. 76, 95% CI(1. 30, 2. 39), Z=3. 66(P＜0. 01)］, Kubota drinking test score［MD=－1. 05, 95% CI(－1. 69, －0. 41), Z=3. 20(P＜0. 01)］, Ichiro Fujima swallowing efficacy score［MD=2. 73, 95% CI(1. 73, 3. 74), Z=5. 31(P＜0. 01)］, VFSS score［MD=1. 81, 95% CI(1. 57, 2. 05), Z=14. 75(P＜0. 01)］, prealbumin［MD=22. 10, 95% CI(10. 65, 33. 54), Z=3. 78(P＜0. 01)］, serum albumin［MD=4. 08, 95% CI(1. 99, 6. 18), Z=3. 82(P＜0. 01)］ and NRS2002 score［MD=－0. 28, 95% CI(－0. 42, －0. 14), Z=3. 85(P＜0. 01)］. Conclusion Acupoint application is effective and reliable in the treatment of dysphagia after stroke, which can be used for clinical promotion. However, the quality and quantity of the literature included in the analysis are limited, and high-quality, large-sample double-blind randomized controlled trials are still needed to provide higher level of evidence. (目的 系统评价穴位敷贴治疗卒中后吞咽障碍的疗效。方法 计算机检Cochrane Library、Web of Science、PubMed、Embase、中国知网(CNKI)、维普数据库(VIP)、万方数据库(Wanfang Data)、中国生物医学文献数据库(CMB)中关于穴位敷贴治疗卒中后吞咽障碍的研究, 检索时限均为数据库建立至2023年1月31日。由两名研究员独立进行文献筛选、数据提取及方法学质量评价后, 采用RevMan 5. 4软件对纳入研究进行Meta分析。结果 共纳入11项RCT/CCT研究, 1018例患者。 Meta分析结果显示, 穴位贴敷治疗脑卒中后吞咽障碍在总有效率［OR=4. 16, 95% CI(2. 65, 6. 53), Z=6. 21(P＜0. 01)］、痊愈率［OR=1. 76, 95% CI(1. 30, 2. 39), Z=3. 66(P＜0. 01)］、洼田饮水试验评分［MD=－1. 05, 95% CI(－1. 69, －0. 41), Z=3. 20(P=0. 001)］、藤岛一郎吞咽疗效评分［MD=2. 73, 95% CI(1. 73, 3. 74), Z=5. 31(P＜0. 01)］、VFSS评分［MD=1. 81, 95% CI(1. 57, 2. 05), Z=14. 75(P＜0. 01)］、前白蛋白［MD=22. 10, 95% CI(10. 65, 33. 54), Z=3. 78(P＜0. 01)］、血清白蛋白［MD=4. 08, 95% CI(1. 99, 6. 18) , Z=3. 82(P＜0. 01)］、NRS2002评分［MD=－0. 28, 95% CI(－0. 42, －0. 14) , Z=3. 85(P＜0. 01)］方面优于对照组。结论 穴位贴敷治疗脑卒中后吞咽困难的疗效可靠, 可用于临床推广。但纳入分析的文献质量和数量有限, 仍需高质量、大样本的双盲随机对照试验提供更高级别的证据。)